Effect of long-haul transmeridian travel on recovery and performance in international level swimmers. Issue 4 (August 2022) - Rossiter, Antonia; Comyns, Thomas M.; Powell, Cormac; Nevill, Alan M.; Warrington, Giles D.
This study holistically examined the effects of long-haul transmeridian travel (LHTT) on physiological, perceptual, sleep and performance markers in nine international level swimmers preparing for the 2019 FINA World Long Course Championships in Gwangju, South Korea. Baseline (BL) measurements were taken over two days during the week before a long-haul eastward flight across eight time-zones. Following the flight, measurements were taken over a six-day holding camp in Japan (C1-C6), and over four days at the competition venue in Gwangju before the Championships commenced (PR1-PR4). Salivary cortisol (sCort), immunoglobulin A (sIgA), alpha-amylase (sAA) concentrations and perceptual measures via the Liverpool John Moore's University Jetlag Questionnaire were assessed. Sleep was monitored using wrist activity monitors and self-report sleep diaries. Performance was assessed via squat jump (SJ), countermovement jump (CMJ) and a 4 × 100 m swim test. Participants perceived themselves to be significantly more fatigued and jet lagged than BL for five- and nine-days post-travel, respectively. Morning sCort decreased by 70% on C1 and remained significantly lower than BL until C6 ( p  < 0.05). Sleep ratings improved significantly in comparison to BL from C5 onwards ( p  < 0.05). Compared with BL, there was no significant change in swim performance or SJ height following travel; however, there was a 3.8 cm improvement ( p  < 0.001) in CMJ height on C5. It took ten days for elite swimmers to perceive themselves recovered from jet lag following LHTT in an eastward direction across eight time-zones. LHTT did not negatively affect sleep or physical performance in the swimmers in comparison to BL.